Abstracts - XIV Brazilian Congress of Pediatric Neurosurgery - Jubé , Paulo Ronaldo (2023)
The XIV Congress of SBNPED, held at the Clarion Hotel, part of the Órion complex in Goiânia, from August 2 to 5, 2023, was truly a significant comeback for in-person events in the field of pediatric neurosurgery. This reunion was characterized by a high scientific standard and also filled with emotion. This edition of the event brought a novelty, as for the first time in Brazil, the ISPN – International Society for Pediatrics Neurosurgery was present with the ISPN Educational Course included in the event's schedule.